Innovative framework for self-service kiosks: Integrating customer value knowledge - Yulia Vakulenko; Pejvak Oghazi; Daniel Hellström (Journal of Innovation & Knowledge (JIK), 2019)
This study reveals different types of self-service kiosk customer value and synthesizes the self-service kiosk customer value framework, which includes four value groups and three types of customer value elements. The study also reveals gaps which stem from the inconsistency and fragmented nature of previous research on customer value in self-service kiosks. Based on the review of relevant literature and analysis of the systematically selected articles, the findings provide a basis for future investigations into service science and support manager decision making during the stages of consideration, implementation, and improvement of self-service kiosk networks. This study provides a comprehensive inventory of self-service kiosk customer value and its elements.
Keywords: 650; Self-service technology; Self-service kiosk; Customer value